(3GdJcJ aj JaSjQ cJGH SjHhjgs - (3CHh GdMLGL jhSa Hf SdeGf Hf YjSi GdfJeQis; (3GdGYde GdTfbQj , jhSa Hf SdjeGf Hf YjSi GdTfJeQj GdCfOdSj, CHh GdMLGL,J (B476 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSYjJf bGd CHh GdMLGL QMeg Gddg CeG HYO aGdahGFO cKjQI eJTYHI hTQa cd Yde HbOQ aGFOJg s
(3BNQgG (B:s
(3aEf dGe GdeYQhaI EPG COZeJ aCHOdJ ddEOZGe abO CYdJ acQghG NPa eG bHdgG dFdG jONdhG YdI Ydi YdI aEYde Pdc hUdi Gddg Ydi eMeO hBdg hUMHg hSde s
(3CdaJg ddedc GdeYJVO HGddg CHh YeQh YHGO Hf eMeO SfI (B440s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B233 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B302s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs